Pengaruh Pemanasan Awal Dexlite dan Biodiesel Minyak Jelantah Terhadap Karakteristik Penyumbatan Pada Fuel Filter - Mukrizal, Rozy; Ghurri, Ainul; Wirawan, I Ketut Gede (Teknik Desain Mekanika; Vol 10 No 4 (2022): Oktober 2022 : Teknik Desain Mekanika, 2022)
Abstract Biodiesel is an alternative fuel that can replace diesel oil as diesel engine fuel. The use of biodiesel as a fuel certainly has drawbacks compared to diesel oil which affects the diesel engine components, one of which is the fuel filter, where the filtered dirt will form deposits so that the fuel filter can be clogged more quickly. The purpose of this study was to examine the effect of preheating the fuel in Dexlite and a mixture of 70% Pertamina Dex and 30% Biodiesel used cooking oil (B30) on the pressure drop, flow velocity, and deposits on the fuel filter. This test is carried out by flowing 400 liters of fuel through the fuel filter by varying the preheating temperature of 50oC, 60oC, and 70oC. The fuel pressure before entering the fuel filter is maintened at 105 kPa. The test results show that the variation of the preheating temperature does not significantly affect the pressure drop, but it does affect the fuel flow rate. The higher preheating temperature makes the higher fuel flow rate entering the fuel filter and leaving the fuel filter. Dexlite test with preheating to 70oC shows the highest flow velocity is 1.36 m/s entering the fuel filter and 1.24 m/s leaving the fuel filter. Keywords: Dexlite, Biodiesel, Fuel Filter, Preheating, Pressure Drop, Flow Velocity